A simple synthesis method for nanostructured Co-WC/carbon composites with enhanced oxygen reduction reaction activity. Issue 1 (1st December 2016) - Kang, Jun; Kim, Hye-min; Saito, Nagahiro; Lee, Myeong-Hoon
Abstract: Co nanoparticles (Co NPs) and nanoscale tungsten carbide (WC) are successfully synthesized simultaneously with mesoporous structured carbon black (C) using an innovative simple method, which is known as solution plasma processing (SPP), and NPs are also loaded onto carbon black at the same time by SPP. The introduction of Co NPs led to not only superior oxygen reduction reaction (ORR) activity in terms of onset potential and peak potential, but also to a more efficient electron transfer process compared to that of pure WC. Co-WC/C also showed durability for long-term operation better than that of commercial Pt/C. These results clearly demonstrate that the presence of Co NPs significantly enhanced the ORR and charge transfer number of neighboring WC NPs in ORR activities. In addition, it was proved that SPP is a simple method (from synthesis of NPs and carbon black to loading on carbon black) for the large-scale synthesis of NP-carbon composite. Therefore, SPP holds great potential as a candidate for next-generation synthetic methods for the production of NP-carbon composites. Abstract :